2011
DOI: 10.1016/j.ccr.2010.10.016
|View full text |Cite
|
Sign up to set email alerts
|

Structural, mechanistic and coordination chemistry of relevance to the biosynthesis of iron–sulfur and related iron cofactors☆

Abstract: Iron-sulfur clusters are an important class of protein-bound prosthetic center that find wide utility in nature. Roles include electron transfer, enzyme catalysis, protein structure stabilization, and regulation of gene expression as transcriptional and translational sensors. In eukaryotes their biosynthesis requires a complex molecular machinery that is located within the mitochondrion, while bacteria exhibit up to three independent cluster assembly pathways. All of these paths share common themes. This revie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 151 publications
(255 reference statements)
1
24
0
Order By: Relevance
“…This is in contrast to our cluster containing control protein Yah1, which has a 4 cysteine coordination environment ligating its tightly bound FeS cluster. 49 Finally, iron-ligand bond lengths we observe are similar to those reported for Fe(II)-binding proteins from other biological systems 50, 51 and to bond lengths we previously reported for yIsu1. 15 …”
Section: Discussionsupporting
confidence: 88%
“…This is in contrast to our cluster containing control protein Yah1, which has a 4 cysteine coordination environment ligating its tightly bound FeS cluster. 49 Finally, iron-ligand bond lengths we observe are similar to those reported for Fe(II)-binding proteins from other biological systems 50, 51 and to bond lengths we previously reported for yIsu1. 15 …”
Section: Discussionsupporting
confidence: 88%
“…The Fe-S proteins contain inorganic iron and sulfur as cofactors (40,47,48). Iron and sulfur are redox active, and the cluster can undergo redox reactions under physiological conditions.…”
Section: Discussionmentioning
confidence: 99%
“…In the cell, however, an extensive machinery has evolved for the formation and incorporation of specific iron-sulfur centers into proteins. It has been shown that the sulfur in iron-sulfur centers originates from cysteine thiol and is transferred as S 0 bound to the sulfurtransferase component in both prokaryotic and eukaryotic systems [222]. …”
Section: H2s Reaction With Metalsmentioning
confidence: 99%